2008
DOI: 10.1101/gad.1678608
|View full text |Cite
|
Sign up to set email alerts
|

A C. elegans genome-scale microRNA network contains composite feedback motifs with high flux capacity

Abstract: MicroRNAs (miRNAs) and transcription factors (TFs) are primary metazoan gene regulators. Whereas much attention has focused on finding the targets of both miRNAs and TFs, the transcriptional networks that regulate miRNA expression remain largely unexplored. Here, we present the first genome-scale Caenorhabditis elegans miRNA regulatory network that contains experimentally mapped transcriptional TF → miRNA interactions, as well as computationally predicted post-transcriptional miRNA → TF interactions. We find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
236
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 223 publications
(257 citation statements)
references
References 72 publications
16
236
1
Order By: Relevance
“…By bioinformatic analysis, Tsang et al (2007) have found that incoherent FFLs are no less common than the coherent types. Similarly, Martinez et al (2008) were able to identify many feedback loops between a transcription factor and a miRNA in the C. elegans genome. In previous reports (Alon 2007), negative feedback loops were rather infrequent, perhaps because only transcription factors were analyzed (TFs).…”
Section: Mirnas and Expression Buffering-evidence From The Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…By bioinformatic analysis, Tsang et al (2007) have found that incoherent FFLs are no less common than the coherent types. Similarly, Martinez et al (2008) were able to identify many feedback loops between a transcription factor and a miRNA in the C. elegans genome. In previous reports (Alon 2007), negative feedback loops were rather infrequent, perhaps because only transcription factors were analyzed (TFs).…”
Section: Mirnas and Expression Buffering-evidence From The Literaturementioning
confidence: 99%
“…A good example of negative feedback loop (Fig. 1E) is given by Martinez et al (2008). In this example, miR is miR-43 and T is lin-26; the latter being expressed in the embryos of C. elegans and involved in epithelial differentiation.…”
Section: Mirnas and Expression Buffering-evidence From The Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…While a genome-wide collection of transcription regulatory interactions has been reported for E. coli and S. cerevisiae, 11,12 transcription regulatory networks for metazoan organisms, including C. elegans, have been mapped experimentally only to a limited extent. In C. elegans, direct transcription factor regulatory interaction networks have been identified through chromatin immunoprecipitation, 13,14 and yeast one-hybrid experiments, [15][16][17] while indirect regulatory interaction networks have mainly been identified through combinations of gene knockout or knockdown and gene reporter, RT-PCR or microarray experiments. [18][19][20][21] In the latter case, cis-regulatory motif finding algorithms have been applied in order to pinpoint the transcription factors directly responsible for the change in gene expression.…”
Section: Introductionmentioning
confidence: 99%